2020
DOI: 10.15415/jmrh.2020.71003
|View full text |Cite
|
Sign up to set email alerts
|

Feeding habits, Overweight, Obesity and Hypertension and Associated Factors among Polytechnic Students in Ekiti State, Southwest Nigeria

Abstract: Overweight and obesity is a risk factor to chronic non-communicable diseases. This study assessed level of overweight/obesity and blood pressure among students of a higher institution in Southwest Nigeria. This cross-section study involved 300 students of a public higher institution in Ado-Ekiti, Southwest, Nigeria. A validated self-administered questionnaire was used to collect data on personal characteristics, feeding pattern and lifestyle of the students. Body Mass Index (BMI) was categorized into normal we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The prevalence of obesity and hypertension is increasing, particularly in the urban areas. [14,15] However, there is limited research on the relationship between obesity and hypertension in the rural areas of southeastern Nigeria. Understanding this relationship in body composition among the eastern population will add to the body of knowledge in anthropometric studies for identifying individuals at risk of hypertension and for developing effective prevention and treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of obesity and hypertension is increasing, particularly in the urban areas. [14,15] However, there is limited research on the relationship between obesity and hypertension in the rural areas of southeastern Nigeria. Understanding this relationship in body composition among the eastern population will add to the body of knowledge in anthropometric studies for identifying individuals at risk of hypertension and for developing effective prevention and treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the number of studies considering how sports vision training affects non-athletes like average university students is limited. Studies have indicated that the rise in technological advancements in the education sector also plays as one of the key factors leading to the problems associated with ocular and physical disorder (Chitkara et al, 2020;Dada & Igbe, 2021). Therefore, the need to investigate the benefits of such training is much more among university students considering the rise of visual skills problems among them.…”
Section: Introductionmentioning
confidence: 99%